MANAJEMEN SDM BERBASIS PSYCHOLOGICAL DETACHMENT: UPAYA OPTIMALISASI KINERJA PENGASUH ASRAMA DI AL WAFI ISLAMIC BOARDING SCHOOL - Muhammad Amiq Azmi; Hasyim Asy'ari (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2026)
Dormitory supervisors (musyrif/musyrifah) at Islamic boarding schools endure high psychological workloads due to the demands of constant student supervision, making them highly susceptible to emotional exhaustion and diminished professionalism. This study examines the implementation of Human Resource Management (HRM) based on psychological detachment as a strategy to mitigate burnout and optimize supervisor performance at Al-Wafi Islamic Boarding School. Utilizing a descriptive qualitative method with a case study approach, data were gathered through in-depth interviews, environmental observations, and regulatory document analysis. The findings reveal that Al-Wafi Islamic Boarding School structurally implements psychological detachment strategies through three core interventions: policies restricting official communication outside shift hours (task segmentation), private living quarters separated from student dormitories, and a horizontal task delegation system (peer-caregiver substitution). This formal job design successfully facilitates the supervisors' energy recovery experiences by severing cognitive attachment to dormitory burdens during off-hours. This study concludes that anchoring psychological aspects within adaptive HRM regulations effectively dismantles the cultural barrier of